(untitled) (Research, Society and Development, 2025)
The objective of the present study is to present a mixed infection by Ancylostoma spp. and Toxocara canis in a puppy, describing the clinical signs, diagnosis, and treatment provided, as well as discussing the possible public health implications, reinforcing the importance of preventing these zoonoses within the context of veterinary and collective medicine. This case report describes a mixed infection by Ancylostoma spp. and Toxocara canis in a seven-month-old mixed-breed female dog, presented during a routine check-up with complaints of pasty stools. Based on anamnesis, physical examination, complete blood count, and fecal parasitological analysis, the presence of both parasites was confirmed. Treatment involved antiparasitic administration and environmental control measures. The discussion highlights the importance of early diagnosis and proper treatment, especially considering the zoonotic potential of these parasites, which pose a significant public health risk. The report reinforces the need for integrated surveillance and health education strategies, aligned with the One Health approach, to effectively control helminth infections in companion animals and prevent human transmission.